Aplastic anaemia and the hypocellular myelodysplastic syndrome: histomorphological, diagnostic, and prognostic features. Issue 11 (November 1985) - Fohlmeister, I; Fischer, R; Mödder, B; Rister, M; Schaefer, H E
Abstract : In a retrospective study of 111 patients with aplastic anaemia iliac crest biopsies were evaluated for the presence of morphological features statistically related to the evolution of the disease. Prognostic variables for a transition to acute non-lymphatic leukaemia were: cellular atypias of the three haemopoietic lineages, as observed in the myelodysplastic syndrome, and especially "micromegakaryocytes"; high numbers or irregular distribution of megakaryocytes, or both; and (slight) marrow fibrosis. Clinical variables did not influence these prognostic correlations. Prognosis in relation to death from bone marrow failure without leukaemia might well have been influenced by a strong plasma cell reaction, but this correlation was weakened by clinical factors. On the basis of this study aplastic anaemia can thus be subdivided morphologically into two disease entities–namely, hypocellular myelodysplastic syndrome with a 23-82% risk of acute non-lymphatic leukaemia developing within three years, depending on how many variables associated with acute non-lymphatic leukaemia are present, and non-dysplastic myelohypoplasia.